Algorithm for the cloud service workflow scheduling with setup time and deadline constraints - Hong SHEN; Xiao-ping LI (Tongxin xuebao)
Cost minimization with deadline constraints and setup time is a new resource allocation optimization problem in cloud computing.An integer programming model is constructed for this NP-hard problem.A novel probability model and updating mechanism is suggested for sampling the solution space.A heuristic method is investigated for generating good initial population.A hybrid estimation of distribution algorithm (HEDA) is proposed for the considered problem.The global best solution is adopted to balance the diversification and intensification of HEDA.Experimental results show that the proposed method is effective to optimize the workflow running cost within reasonable CPU time.